Considerations of HLA, Renal Failure, Valproic Acid Use, and Current Treatment Guidelines in Clozapine-Induced Agranulocytosis - Melissa Sussman; Michael Epifania; Derrick Eng; Yun Jae Cho; Richard Steward (Case Reports in Psychiatry)
Clozapine, the choice atypical antipsychotic for refractory schizophrenia, schizoaffective disorder, and bipolar disorder, has been shown to reduce positive and negative symptoms of schizophrenia. Clozapine, though beneficial in reducing the need for hospitalization, rehabilitation, and health care costs, is known as a drug of last resort due to its potential adverse event of clozapine-induced agranulocytosis, which holds a case fatality rate between 4.2 and 16%. Herein, we describe a female patient with longstanding schizoaffective disorder and chronic kidney disease who suffered from clozapine-induced agranulocytosis after failing two other atypical antipsychotics. Retrospective considerations of this case and management highlight risk factors such as HLA status, renal failure, and concurrent valproic acid use which presently do not have official screening, guidelines, or restrictions in place when prescribing clozapine. Additionally, there are no specific clozapine-induced agranulocytosis management recommendations such as G-CSF/filgrastim dose, timing of bone marrow aspirate and biopsy, and use of concomitant valproate. We propose that further comprehensive official screening, monitoring, and guidelines in the prescribing of clozapine, and further guidelines in the treatment of clozapine induced agranulocytosis, could increase the cost-effectiveness of clozapine treatment, and decrease the incidence, and morbidity of this feared adverse event.